2016
DOI: 10.4238/gmr.15028315
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus (HPV), distribution of HPV types, and risk factors for infection in HPV-positive women

Abstract: ABSTRACT. The aim of this study was to describe the prevalence of human papillomavirus (HPV), the distribution of different HPV types, and the putative risk factors for infection among HPV-positive women from the State of Alagoas, Northeast Brazil. We analyzed data from 515 patients attending public and private health centers. HPV DNA from cervical samples was extracted and HPV genotyping was performed by polymerase chain reaction using MY09/11 consensus primers followed by direct sequencing. The chi-squared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
1
7
0
1
Order By: Relevance
“…Other studies in Brazil showed a prevalence of 42.4% for HPV 16 found in HSIL, 63.1% of cases of CIN3 and, in the rest of world, the prevalence of HPV 16 found in HSIL was around 45% [29, 36, 37]. In the agreement, other studies in Northeastern Brazil have also found HPV 16 to be the most prevalent HPV type in women with cervical lesions [14, 3134]. In contrast to our data, another study carried out in the Northeast region of Brazil found the HPV 31 to be the most prevalent among women with normal and abnormal cytological outcomes [30].…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Other studies in Brazil showed a prevalence of 42.4% for HPV 16 found in HSIL, 63.1% of cases of CIN3 and, in the rest of world, the prevalence of HPV 16 found in HSIL was around 45% [29, 36, 37]. In the agreement, other studies in Northeastern Brazil have also found HPV 16 to be the most prevalent HPV type in women with cervical lesions [14, 3134]. In contrast to our data, another study carried out in the Northeast region of Brazil found the HPV 31 to be the most prevalent among women with normal and abnormal cytological outcomes [30].…”
Section: Discussionsupporting
confidence: 67%
“…In Northeastern Brazil, a number of papers have been published on HPV prevalence and type distribution among women with cytological and/or histological alterations [14, 3035]. However, to the best of our knowledge, HPV prevalence among women with cervical lesions in the state of Sergipe, located in this region, has never been assessed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals who do not use condoms are at higher risk of infection and reinfection by HPV and other STIs, which also contribute to cervical lesions progression [ 33 , 34 ], probably leading to the chronic local inflammatory process and intensified immune system stimulation [ 12 , 19 , 35 ]. In contrast, the constant use of condoms is associated with a lower risk of HPV infection and regression of cervical lesions rates, as it allows the immune system to act and repair the damaged tissue, preventing the progression of the lesion.…”
Section: Discussionmentioning
confidence: 99%